A comparison of public library use of statistics – a cross‐country survey report - Liu, Yan Quan (New Library World, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilizing statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight differences and similarities of the uses the two countries’ directors make of statistics and the statistical information that directors find particular useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
Keywords: China; Librarians; Libraries; Management; Statistics; USA; dept.ils

The use of statistics in the managerial process by public library directors in China and the USA: a cross‐country survey - Liu, Yan Quan (Library Management, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilising statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight the differences and similarities between the ways in which the two groups of directors make use of statistics, and the statistical information that directors find particularly useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process, and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
Keywords: China; Libraries; Management; Public Libraries; Statistics; USA; dept.ils

The use of national public library statistics by public library directors - Liu, Yan Quan; Zweizig, Douglas L (The Library Quarterly, 2001)
Keywords: dept.ils; ⛔ No DOI found